PENGEMBANGAN DAN PEMBERDAYAAN INDUSTRI RUMAH TANGGA (IRT) JAMUR TIRAM DI DESA PONTANG, KECAMATAN AMBULU, KABUPATEN JEMBER - Piluharto, Bambang; Ubaidillah, Firdaus; Triono, Agus (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
Home industry Oyster Mushroom “Kayla” which is located in Dusun Tengan RT 47 RW 12 Pontang Village, Ambulu District, Jember Regency is a business unit that produces oyster mushrooms. This home industry’s production capacity is 5 kgs of mushrooms per day, with the main consumers being melijo traders and the sorrounding community. The demand for mushrooms from customers is often not met due to limited production capacity. Mushroom baglog as a growth medium is an important component in mushroom production. So far, Mushroom baglogs have been suplied from self-made baglogs and purchased from other parties. Self-made baglogs was produced manually by hand. This is inefficient, besides purchasing baglog from other parties also increases production costs. This activity aims to provide training and assistance to partners, namely the oyster mushroom home industry “Kayla” as a form of training in production of mushroom baglog using the baglog press technique along with digital marketing technique. To achieve this goal, the methods used include training and assistance to activity partners. From the results obtained, the activity partners were independently able to carry out production using the baglog press technique. Apart from that, digital marketing development using social media has been carried out to market mushroom products. The impact obtained from this activity is an increase in the number of baglog obtained, thereby increasing mushroom production capacity to around 10 kgs/day. In the future, skill development and economic empowerment of activity partners can be continued with an emphasis on training on mushroom – based product diversification.